2014
DOI: 10.1371/journal.pone.0111736
|View full text |Cite
|
Sign up to set email alerts
|

Age Is a Critical Risk Factor for Severe Fever with Thrombocytopenia Syndrome

Abstract: BackgroundSevere Fever with Thrombocytopenia Syndrome (SFTS) is an emerging infectious disease in East Asia. SFTS is a tick borne hemorrhagic fever caused by SFTSV, a new bunyavirus named after the syndrome. We investigated the epidemiology of SFTS in Laizhou County, Shandong Province, China.MethodsWe collected serum specimens of all patients who were clinically diagnosed as suspected SFTS cases in 2010 and 2011 in Laizhou County. The patients' serum specimens were tested for SFTSV by real time fluorescence qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 19 publications
8
57
0
Order By: Relevance
“…Furthermore, we found that the rate of SFTSV-IgG seropositivity was consistent among male and female tea pluckers, but was much higher among men than women for all participants. Ding et al showed that age is a critical risk factor for SFTS morbidity and mortality (17). In our study, we found that age is also a risk factor for SFTSV infection.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, we found that the rate of SFTSV-IgG seropositivity was consistent among male and female tea pluckers, but was much higher among men than women for all participants. Ding et al showed that age is a critical risk factor for SFTS morbidity and mortality (17). In our study, we found that age is also a risk factor for SFTSV infection.…”
Section: Discussionsupporting
confidence: 67%
“…We used an enzyme-linked immunosorbent assay kit obtained from the National Institute for Viral Disease Control and Prevention and followed its instructions to test for SFTSV-specific immunoglobulin G (IgG) antibodies in sera samples (17,18). A sample of 100μl (1μl sera diluted in 100μl total sample) was added to each well and incubated at 37°C for 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggested that age and occupation were potential risk factors of SFTSV infection in general population of Penglai County. The positive rate in this study was similar to the reported percentage (3.3%) recorded in Shandong Province 14 . However, it was much higher than that reported in Jiangsu (0.44%), lower than that in Shanxi (4.7%) 15,16 .…”
Section: Discussionsupporting
confidence: 90%
“…Recently SFTSV RNA has been detected from rodents and Asian house shrews in China [44].These data demonstrated that the domesticated animals, rodents and shrews have been widely infected by SFTSV in the endemic areas and they may act as amplifying hosts of SFTSV and play a major role in SFTSV transmitting. Approximately 1%e3% rural population in endemic area in China was infected with SFTSV [37e39, 45]. The SFTSV antibody positive rate was not significantly different among people at different age groups, but hospitalized SFTS patients were mainly middle and old aged populations and death mainly occurred in people old than 50 years old, suggesting age is a critical risk factor for severe disease and death of SFTS [45].…”
Section: Vectors Hosts and Transmission Routinementioning
confidence: 99%
“…Approximately 1%e3% rural population in endemic area in China was infected with SFTSV [37e39, 45]. The SFTSV antibody positive rate was not significantly different among people at different age groups, but hospitalized SFTS patients were mainly middle and old aged populations and death mainly occurred in people old than 50 years old, suggesting age is a critical risk factor for severe disease and death of SFTS [45]. Clusters of SFTS cases have been reported in several provinces in China [1,46e50], suggesting a human-to-human transmission model of the disease.…”
Section: Vectors Hosts and Transmission Routinementioning
confidence: 99%